Life beyond the stethoscope. (1st February 2014) - Richards, Kate
Abstract : Kate Richards is Deputy Director of Strategic Business Planning at the Ministry of Justice. She explains how she has used the skills honed as a vet in non‐veterinary roles within the Civil Service